PEMANFAATAN MEDIA SOSIAL TIKTOK SEBAGAI MEDIA PROMOSI UNTUK PENGENALAN PRODUK PERBANKAN DI BSI MELALUI AKUN TIKTOK @Lifewithbsi - Diassyahma, Feriza; Ansori, Miswan; feriza (Wahana Islamika, 2025)
This article examines the digital promotion strategy implemented by Bank Syariah Indonesia (BSI) through its TikTok account @Lifewithbsi in introducing Islamic banking products to younger audiences. The study is grounded in the growing role of social media—particularly TikTok—as a central medium for visual and symbolic communication among digital natives. The research aims to analyze BSI’s visual-narrative strategy and evaluate the effectiveness of promotional content in increasing audience awareness and interest. Employing a qualitative approach with a descriptive-explorative design, the study adopts digital ethnography as its main method. Data were collected through a seven-day intensive observation of video content, captions, comments, and user interactions on the @Lifewithbsi account. Findings reveal that BSI utilizes a storytelling-based promotion model, light symbolic religious messaging, and creative visual formats aligned with TikTok’s algorithmic culture. Content effectiveness is evident through high engagement levels on emotionally and informatively resonant posts. This strategy successfully enhances brand proximity and reinforces positive perceptions of BSI’s Islamic banking services. The study concludes that TikTok functions not only as a promotional platform but also as a symbolic space for shaping digital religious identity and communicatively expanding Islamic banking’s market reach through aesthetic and participatory means.